Dictionary of Labour Biography
XVII, 327 p.
Keywords: Includes radicals of the Chartist and earlier periods, trade unionists and other radicals after 1850. The book is especially concerned with 20th-century activists and intellectuals, notably those whose formative years or main political life was spent during the period between the two World Wars.